Analysis of lactate, heart rate and rating of perceived exertion responses in randori, competition and specific evaluation of judo - Souza, A. L. B.; Tavares Junior, A. C.; de Padua Gomes, F.; da Silva, H. S.; Dos-Santos, J. W.; Souza, M. R. M.; Moreira Junior, M. E.; da Silva, W. L. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. Blood lactate [La-], heart rate (HR) and rating of perceived exertion (RPE) have been used to quantify the intensity of effort in judo. Problem and Aim. The relationship among the variables, [La-], HR and RPE after the first fight in the official competition (1-OC), one Randori (RAN), and the Special Judo Fitness Test (SJFT) have not been studied together. Therefore, the present study aimed to verify the correlations among [La-], HR and RPE in the RAN, 1-OC and SJFT, and the change of these variables in the three conditions. Methods. The sample consisted of 16 state and national level judokas, 8 men and 8 women, aged: 18 ± 0.9. Anthropometric assessment, SJFT and RAN were conducted in the first week and in the second one, judokas participated in the competition. HR, RPE and [La-] were collected in the SJFT and RAN, while in the 1-OC, only RPE and [La-] were collected. Results. [La-] differed amongst the three situations, with higher values in the SJFT followed by the 1-OC and RAN. In relation to RPE, SJFT also presented higher values in relation to the 1-OC. There was a high correlation between HRmed and RPE in the SJFT and between HRmax and [La-] in the RAN. Conclusions. For the category studied, [La-] best discriminated the specific actions of judo, the HR did not seem to be a good indicator of the intensity of the specific activities of judo. More studies with RPE in training sessions and complete competitions must be held to add new information to the results found.